(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
يقال عن فضاء تبولوجي إنه فضاء إذا كانت كل مجموعة متراصة فيه مجموعة مغلقة, ويقال عن فضاء تبولوجي إنه فضاء أصغري( ) إذا كان فضاء وكان من أجل أية تبولوجيا على مثل و بحيث لا يكون فضاء . لقد قمنا في هذا البحث بدراسة - تبولوجيا والعلاقة بين - تبولوجيا و - تبولوجيا. Let be a topological space,we say that is -space if every compact subset of is closed in , -space is called Minimal - space if every topology of such that implies is not a -space. In this research we will study -topology and the relation between -topology and -topology.